Hi,
I have this equation and I need to solve for m... could someone please please help me??
A - m*B = (n*A - m*C) / (1+R)
Well, let's see...
$\displaystyle A-mB=\frac{(nA-mC}{1+R}$
$\displaystyle A(1+R)-mB(1+R)=nA-mC$
$\displaystyle -mB(1+R)=nA-mC-A(1+R)$
$\displaystyle -mB(1+R)+mC=nA-A(1+R)$
$\displaystyle mB(1+R)-mC=A(1+R)-nA$
$\displaystyle m(B(1+R)-C)=A(1+R)-nA$
$\displaystyle m=\frac{A(1+R)-nA}{B(1+R)-C}$
I checked over this once and didn't see any errors. I hope I didn't overlook anything. I also see that math_helper has already attached a solution. I see it is equivalent to my own. Take your choice.